Colombian Essential Oil of Ruta graveolens against Nosocomial Antifungal Resistant Candida Strains (2021)
Drug resistance in antifungal therapy, a problem unknown until a few years ago, is increasingly assuming importance especially in immunosuppressed patients and patients receiving chemotherapy and radiotherapy. In the past years, the use of essential oils as an approach to improve the effectiveness of antifungal agents and to reduce antifungal resistance levels has been proposed. Our research aimed to evaluate the antifungal activity of Colombian rue, Ruta graveolens, essential oil (REO) against clinical strains of Candida albicans, Candida parapsilopsis, Candida glabrata, and Candida tropicalis. Data obtained showed that C. tropicalis and C. albicans were the most sensitive strains showing minimum inhibitory concentrations (MIC) of 4.1 and 8.2 µg/mL of REO. Time–kill kinetics assay demonstrated that REO showed a fungicidal effect against C. tropicalis and a fungistatic effect against C. albicans. In addition, an amount of 40% of the biofilm formed by C. albicans was eradicated using 8.2 µg/mL of REO after 1 h of exposure. The synergistic effect of REO together with some antifungal compounds was also investigated. Fractional inhibitory concentration index (FICI) showed synergic effects of REO combined with amphotericin B. REO Lead a disruption in the cellular membrane integrity, consequently resulting in increased intracellular leakage of the macromolecules, thus confirming that the plasma membrane is a target of the mode of action of REO against C. albicans and C. tropicalis.